2021
DOI: 10.1097/j.jcrs.0000000000000602
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis after pediatric cataract surgery in the United States: report using an insurance claims database

Abstract: The incidence of postoperative endophthalmitis after pediatric cataract surgery occurs more frequently and is detected later than previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…In adults the incidence rate is estimated to be about 0.04% [39,40]. A recent retrospective cohort study using claims data from Optum's deidentified Clinformatics Data Mart Database showed that in children younger than 13 years there is a 0.51% incidence of endophthalmitis within 90 days following cataract surgery [41 ▪ ]. This study noted a slightly higher rate of endophthalmitis after pediatric cataract surgery compared to previous studies, which show more variable incidence rates [42–45].…”
Section: Surgical Techniquementioning
confidence: 43%
“…In adults the incidence rate is estimated to be about 0.04% [39,40]. A recent retrospective cohort study using claims data from Optum's deidentified Clinformatics Data Mart Database showed that in children younger than 13 years there is a 0.51% incidence of endophthalmitis within 90 days following cataract surgery [41 ▪ ]. This study noted a slightly higher rate of endophthalmitis after pediatric cataract surgery compared to previous studies, which show more variable incidence rates [42–45].…”
Section: Surgical Techniquementioning
confidence: 43%